Glutamate receptor antagonists with the potential for migraine treatment. (2nd December 2017) - Ferrari, Anna; Rustichelli, Cecilia; Baraldi, Carlo
ABSTRACT: Introduction : Preclinical, clinical, and other (e.g., genetic) evidence support the concept that migraine susceptibility may at least partially result from a glutamatergic system disorder. Therefore, the receptors of the glutamatergic system are considered relatively new targets for investigational drugs to treat migraine. Investigational and established glutamate receptor antagonists (GluRAs) have been shown to possess antinociceptive properties in preclinical models of trigeminovascular nociception and have been evaluated in clinical trials. This review focuses on preclinical and clinical studies of GluRAs for the treatment of migraine. Areas covered : A PubMed database search (from 1987 to December 2016) and a review of published studies on GluRAs in migraine were conducted. Expert opinion : All published clinical trials of investigational GluRAs have been unsuccessful in establishing benefit for acute migraine treatment. Clinical trial results contrast with the preclinical data, suggesting that glutamate (Glu) does not play a decisive role after the attack has already been triggered. These antagonists may instead be useful for migraine prophylaxis. Improving patient care requires further investigating and critically analyzing the role of Glu in migraine, designing experimental models to study more receptors and their corresponding antagonists, and identifying biomarkers to facilitate trials designed to target specific subgroups of migraine patients.